2018
DOI: 10.1590/0101-60830000000173
|View full text |Cite
|
Sign up to set email alerts
|

Association of mindfulness and impulsivity with obesity

Abstract: Background: The prevalence of obesity has more than doubled over the past three decades. Impulsivity is a multidimensional personality trait that potentially contributes to the development and maintenance of obesity. Mindful awareness can potentially minimize the automatic and inattentive reactions around food. Objectives: In our study, we aimed to research the relationship between impulsivity and mindful attention. Methods: The study population consisted of 60 outpatients aged 18 and older, with a body mass i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(35 reference statements)
1
1
0
2
Order By: Relevance
“…Thus, comparing the age difference of dispositional mindfulness in the knee OA population is required to clarify it. About BMI, our study presents that dispositional mindfulness was not significantly associated with BMI, which is similar to previous studies in the chronic medical condition of type 2 diabetes [11], cardiac disease [8], and obesity [41] population. In contrast, the general health population found that high dispositional mindfulness levels had a low BMI score [42,43].…”
Section: Discussionsupporting
confidence: 90%
“…Thus, comparing the age difference of dispositional mindfulness in the knee OA population is required to clarify it. About BMI, our study presents that dispositional mindfulness was not significantly associated with BMI, which is similar to previous studies in the chronic medical condition of type 2 diabetes [11], cardiac disease [8], and obesity [41] population. In contrast, the general health population found that high dispositional mindfulness levels had a low BMI score [42,43].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we investigated the relationship between mindfulness, impulsivity and addictive smartphone use. Prior evidences have shown that impulsivity is associated with mindfulness [ 80 , 81 ] and addictive behaviour [ 82 , 83 ]. Consistent with previous studies, BIS scores showed significant correlations with FFMQ-SF, MAAS and SAPS scores in this study’s correlation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Isto se deve a maior consciência dos sinais físicos do corpo, como o reconhecimento do nível de fome e saciedade, atenção ao ritmo do comer, características do ambiente e do alimento (Dunn, et al, 2018), que auxilia no controle do consumo excessivo de alimentos e no consumo daqueles de alto teor calórico. Outra explicação é que a atenção plena está negativamente associada a impulsividade, fazendo com que a maior consciência ao momento presente diminua a impulsividade e, consequentemente, o comer excessivo e emocional (Bal, et al, 2018).…”
Section: Discussionunclassified